The Grammatical Disagreement of Praise and Defamation Among Ancient and Modern Scholars/ الخلاف النحوي في عرض "نعم وبئس" قديما وحديثا - Abdul Rashid, Khadijah Khalilah; Mohamad Isa, Abdul Azim (Ijaz Arabi Journal of Arabic Learning, 2024)
The main objective of this study is to present the topic of “praise and defamation” among ancient and modern scholars’ writings. This study covers the elaboration of literal and terminological definitions of this topic, related contents of this topic in their writings, and the methodologies used in arranging the contents of this topic in their writings. This study employs inductive analytical methods and focuses on an inductive approach. It relies on references such as Amali Ibn al-Shajari, al-Kitab by Sibawayh, and al-Muqtadab by al-Mubarrad to clarify the positions of ancient grammarians. This study also reviews Jami’ al-Durus al-Arabiyah by al-Ghalayini, and al-Tatbiq al-Nahwi by Abduh al-Rajhi to represent the positions of modern grammarians, and other books from ancient and contemporary scholars to achieve the objective of this study. This study contributes to educators and students in teaching and learning the Arabic language, especially in Arabic syntax, and empowering the use of their Arabic skills. The result of the study indicated differences between ancient and modern scholars in clarifying the topic of “praise and defamation” in their writings, with Ibn al-Shajari offering a clear explanation of this topic in his book.